2020
DOI: 10.3390/jcm9082576
|View full text |Cite
|
Sign up to set email alerts
|

Limited Mandibular Movements as a Consequence of Unilateral or Asymmetrical Temporomandibular Joint Involvement in Juvenile Idiopathic Arthritis Patients

Abstract: This study aimed to assess the asymmetry of the lower face and motor dysfunction of the masticatory system resulting from unilateral or asymmetrical bilateral temporomandibular joint (TMJ) involvement in juvenile idiopathic arthritis (JIA) patients. The study consisted of clinical examination and cone beam computed tomography (CBCT) of TMJs. Statistical analysis showed correlations between several factors: facial asymmetry and mandibular lateral deviation; the direction of mandibular deviation and the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, some authors related the presence of TMD (21;30) without using or reporting the use of RDC/TMD or DC/TMD -Diagnostic Criteria for Temporomandibular Disorders (Schiffman et al, 2015;Schiffman et al, 2016). Some authors reported the presence of patients with and without TMJ pain [21,23,26,27,30]. Abramowicz et al, 2011 did not evaluate the presence of pain.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors related the presence of TMD (21;30) without using or reporting the use of RDC/TMD or DC/TMD -Diagnostic Criteria for Temporomandibular Disorders (Schiffman et al, 2015;Schiffman et al, 2016). Some authors reported the presence of patients with and without TMJ pain [21,23,26,27,30]. Abramowicz et al, 2011 did not evaluate the presence of pain.…”
Section: Samplementioning
confidence: 99%
“…Regarding ILAR classi cation criteria (Krumrey, et al, 2001), among all 227 JIA patients, 6 (2.6%) presented systemic arthritis, 43 (18.9%) oligoarthritis, and 11 (4.8%) had oligoarthritis extended, 117 (51.5%) presented polyarthritis, being 6 (5.2%) with rheumatoid factor positive polyarthritis, 82 (70%) rheumatoid factor negative polyarthritis and 29 (24.8%) patients in three studies were designated as polyarthritis, without specifying the type [21,27,30]. Also, 29 (12.8%) patients had psoriatic arthritis, 13 (5.7%) enthesitis-related arthritis and 8 (3.5%) other classi cation.…”
Section: Samplementioning
confidence: 99%
“…RME affects not only midpalatal suture, but also circumaxillary sutures [ 6 ]. Although it is a treatment commonly used by clinicians, it might present some disadvantages: when the appliance is anchored to permanent teeth, it might cause their buccal tipping, root resorption, bone fenestration, and reduced buccal bone thickness [ 7 , 8 ]. To avoid these effects, palatal expansion in growing patients can be achieved by using primary teeth as anchorage [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These refer to clinical multi-cause disorders in the morphological and functional system, including tissues and organs within the oral cavity and the facial skeleton (bones and soft tissues, cartilaginous joints). Therefore, the disorders in the area of the temporomandibular joint (TMJ), ankyloses of various origin, occlusion disorders, hyperplasia or hypoplasia of condylar processes of the mandible, cysts and tumors may change the course of the mandible's development [5,13,14]. In addition, the proper growth in the posterior direction [15] and the resistance to compressive forces [16] may be disturbed by some disorders.…”
Section: Introductionmentioning
confidence: 99%